Behavioral Intervention Innovation on Reducing Sexual Risk Behavior among HIV-Positive Men Sex Men: A Literature Review - Melly Rahmayani; Agung Waluyo (Alta Dharma Publisher, 2020)
The high degree of HIV transmission in the MSM circles resulted from the risky sexual behaviors. The study aimed to describe the behavioral intervention innovation to reduce sexual risk behavior among HIV-Positive MSM. This literature study was conducted to identify behavioral intervention innovations among HIV-Positive MSM. Articles were retrieved from Wiley Online, ProQuest, and ScienceDirect databases. The keywords used were behavioral Intervention, sexual risk behavior, and HIV-Positif MSM. The articles were limited based on inclusion criteria: English language full-text articles have been published from 2010 to 2019. Research studies also included several study design types, including a quasi-experimental study, a randomized control trial (RCT), and mixed-method design. Based on the research results on the selected journal, it is known that there is a wide range of behavioral therapy Innovations as an intervention carried out to reduce the sexual risk behavior among HIV-Positive MSM. Several interventions enhance the knowledge about HIV among HIV-Positive MSM, including integrated community and clinic-based intervention, Internet application, small group intervention, social network intervention, the treatment advocacy program, and brief Internet-based group intervention. In addition, man to man Sexual Health Seminar, Positive Sexual health (PoSH), Men speaking out, and community-based peer education can significantly decrease the sexual risk behavior, increase HIV tests improve attention, and search for health facilities. Behavioral intervention is an intervention that is part of nursing intervention, particularly in the hard-to-reach HIV-Positive MSM, because it is a minority group. With innovations, interventions are made more attractive and more convenient so that they are expected to change behaviors, especially sexual risk behavior that can transmit HIV and sexually transmitted diseases. This behavioral innovation tends to be more effective and can be applied in all countries, including developing countries, to reach all areas like those in Indonesia with extensive regions